Exploring the prognostic differences in patients of Chiari malformation type I with syringomyelia undergoing different surgical methods - Zhang, Mingchu; Hu, Yan; Song, Dengpan; Duan, Chengcheng; Wei, Mingkun; Zhang, Longxiao; Lei, Shixiong; Guo, Fuyou (Frontiers in Neurology, 2023)
Abstract: Background: The best surgical treatment of Chiari malformation patients with syringomyelia remains controversial, and whether cerebellar tonsillectomy should be performed has not been decided. Objective: To evaluate the efficacy of posterior fossa decompression with duraplasty (PFDD) and Posterior fossa decompression with resection of tonsils (PFDRT) in patients of Chiari malformation type Ⅰ (CM-Ⅰ) with syringomyelia and explore relevant factors affecting prognosis. Patients and methods: We retrospectively analyzed 182 adult patients of CM-Ⅰ with syringomyelia who underwent PFDD or PFDRT over a 6-year period, and analyzed their clinical manifestations, imaging features, and follow-up data. Clinical outcomes were assessed using the Chicago Chiari Outcome Scale (CCOS), and imaging outcomes were assessed using the syrinx remission rate. Difference comparisons were performed to compare the differences between different surgical groups. Influencing factors associated with outcome were investigated using bivariate analysis and multiple linear regression analysis. Results: There were statistically significant differences in CCOS score (p=0.034) and syrinx remission rates (p=0.046) between the PFDRT group and the PFDD group after surgery. Regression analysis showed that preoperative motor dysfunction, cerebellar-related symptoms and different surgical methods may have influenced the CCOS score and that brainstem-related symptoms and age may have influenced the syrinx remission rates in the total patient group (p<0.05). Regression analysis showed that the duration of symptoms, cerebellar-related symptoms and preoperative syrinx diameter may have influenced the CCOS score and that the preoperative cerebellar tonsillar hernia distance may have influenced the postoperative syrinx remission rate in the PFDRT group (p<0.05). Age and length of hospital stay may have influenced the CCOS score, and brainstem-related symptoms and age may have influenced the syrinx remission rates in the PFDD group (p<0.05). Conclusion: This study showed that the CCOS score in the PFDRT group was better than that in the PFDD group. Preoperative motor dysfunction, cerebellar-related symptoms, and different surgical methods in patients of CM-Ⅰ with syringomyelia affected postoperative CCOS score. Both the duration of symptoms and the age of the patients should be actively considered as factors influencing prognosis. Symptomatic CM-Ⅰ patients with syringomyelia should undergo surgical treatment as early as possible.